Kiss me, Kate! [compact disc] : 2019 Broadway cast recording - Porter, Cole, 1891-1964 (Ghostlight Records, 2020)
Cole Porter's classic musical comes back to the Broadway stage in an updated production featuring Kelli O'Hara, Will Chase, Stephanie Styles, and Corbin Bleu.